Associations between lifestyle factors and acute respiratory infection incidence at Mayen Primary Health Clinic - Meliala, Yose Marselius A.P.; Nasution, Sri Lestari Ramadhani; Suhartina, Suhartina; Nadapdap, Thomson Parluhutan; Sulistijanto, Eddy; Liena, Liena; Rezeki, Naomi Grace; Syahputra, Ari Denggan; Putri, Nadya Nazimuddin (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Background: Acute Respiratory Infections (ARI) remain a significant global health burden with high morbidity, particularly in developing nations. Modern lifestyle shifts—characterised by smoking habits, poor dietary patterns, physical inactivity, and compromised sleep quality—alongside environmental pollution, are hypothesised to contribute to susceptibility to these infections. Objective: This study aims to analyse the association between lifestyle factors (smoking, diet, physical activity, sleep quality) and environmental pollution exposure with the incidence of ARI among patients at the Mayen Primary Clinic in 2023–2024. Methods: This study employed an analytic observational design with a cross-sectional approach. The research was conducted at the Mayen Primary Clinic, Medan, involving 82 respondents selected via consecutive sampling. Data were collected using medical records and validated lifestyle questionnaires, followed by analysis using the Chi-Square test. Results: The findings revealed that the majority of respondents were suffering from ARI (85.4%). Bivariate analysis demonstrated significant correlations between ARI incidence and smoking habits (p<0.001), dietary patterns (p=0.001), sleep quality (p<0.001), and air pollution exposure (p<0.001). However, no significant association was observed between physical activity and ARI incidence (p=0.601). Conclusion: Unhealthy lifestyles and environmental pollution are primary determinants of ARI incidence in primary care settings, necessitating health interventions focused on behavioural modification and environmental control.